Real-Time PCR for Diagnosing and Quantifying Co-infection by Two Globally Distributed Fungal Pathogens of Wheat - Abdullah, Araz S.; Turo, Chala; Moffat, Caroline S.; Lopez-Ruiz, Francisco J.; Gibberd, Mark R.; Hamblin, John; Zerihun, Ayalsew (Frontiers in Plant Science, 2018)
Co-infections – invasions of a host-plant by multiple pathogen species or strains – are common, and are thought to have consequences for pathogen ecology and evolution. Despite their apparent significance, such infections have received limited attention; in part due to lack of suitable quantitative tools for monitoring of co-infecting pathogens and their dynamics. Here, we report on a duplex real-time PCR assay that simultaneously distinguishes and quantifies co-infections by two globally important fungal pathogens of wheat: Pyrenophora tritici-repentis and Parastagonospora nodorum. These fungi share common characteristics and host species, creating a challenge for conventional disease diagnosis and subsequent management strategies. The assay uses uniquely assigned fluorogenic probes to quantify fungal biomass as nucleic acid equivalents. The probes provide highly specific target quantification with accurate discrimination against non-target closely related fungal species and host genes. Quantification of the fungal targets is linear over a wide dynamic range (5000 to 0.5 pg DNA µl-1) with high reproducibility (RSD ≤10%). In the presence of host DNA in the assay matrix, fungal biomass can be quantified up to a fungal to wheat DNA ratio of 1 to 200. The utility of the method was demonstrated using field samples of a cultivar sensitive to both pathogens. While visual and culture diagnosis suggested presence of only one of the pathogen species, the assay revealed not only presence of both co-infecting pathogens (hence enabling asymptomatic detection), but also allowed quantification of relative abundances of the pathogens as a function of disease severity. Thus, the assay provides for accurate diagnosis; and is suitable for high-throughput screening of co-infections for epidemiological studies, and exploring pathogen-pathogen interactions and dynamics, none of which would be possible with the conventional approaches.